Effects of an aqueous leaf extract of Sansevieria senegambica Baker on plasma biochemistry and haematological indices of salt-loaded rats - Ayalogu, Edward; Ikewuchi, Catherine; Onyeike, Eugene; Ikewuchi, Jude (South African Journal of Science, 2011)
The effects of an aqueous extract of the leaves of Sansevieria senegambica on plasma marker enzymes, plasma chemistry and the haematological profile of salt-loaded rats were studied. The control group received only a commercial feed, whilst the four test groups received a diet consisting of the commercial feed and salt, although the reference treatment group was reverted to the normal feed at the end of 6 weeks. The extract was orally administered daily at 150 mg/kg or 200 mg/kg body weight to two test groups, respectively; whilst the test control, reference and control groups received equivalent volumes of water by the same route. The extract had no negative effects on markers of liver and kidney functions, but it did produce leukocytosis, significantly increased (p < 0.05) plasma calcium and potassium levels and significantly decreased (p < 0.05) plasma sodium and chloride levels in the test animals compared to the test control animals. This result supports the traditional use of Sansevieria senegambica in the management of hypertension, whilst suggesting that the extract may be a potassium-sparing diuretic whose mechanism of antihypertensive action may be achieved through alteration of plasma sodium and potassium balances, or through calcium-mediated changes in vascular muscle tone.